Utilization of Coding-Based Deep Learning and Artificial Intelligence (AI) in Improving Students' Digital Skills at SMPN 1 Mataram - Ghina Sufiani Sukma; Gina Soniya (Penerbit Presisi Pustaka, 2026)
The development of digital technology encourages junior high schools to adapt in order to enhance students’ digital literacy competencies. This study examines the implementation of coding instruction and artificial intelligence (AI) to improve students’ digital skills at SMPN 1 Mataram. Using a descriptive qualitative method, the research was conducted through classroom observations and analysis of AI technology integration within the school environment. The findings indicate that the integration of coding and AI enhances students’ computational thinking skills, creativity, and understanding of digital technologies. Additionally, AI supports teachers in personalizing learning, analyzing student learning data, and providing interactive media that aligns with Project-Based Learning (PJBL). Therefore, the utilization of coding and AI contributes significantly to creating an innovative, adaptive, and relevant learning process that meets current technological developments.